Practices of Business Owners on Total Quality Management Concepts on Small Enterprises Along Novaliches, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the practices of business owners on total qualitymanagement concepts in small enterprises along Novaliches, Quezon City, in terms ofleadership, policy and strategy, people, partnership and resources, and process.The result of this study reveals that the small enterprise business owners in Novaliches,Quezon City are mostly sole proprietorships, operated a business for six years and above,and have 10-15 employees; the practices of total quality management concepts evaluated as"fully practice" in terms of leadership, policy and strategy, people, partnership and resources,and process; the most encountered challenges by the business owners on practices of totalquality management concepts is the improper channel of communication, and there is anaction plan proposed for it.The study recommended that the business should maintain its current level of total qualitymanagement and continuously improve it in order to promote its better development. It is alsorecommended that total quality management concepts should be fully utilized at all timeswhen it comes to leadership, policy and strategy, people, partnership and resources, andprocesses to keep the business in better shape. It is advised that business owners shouldmake it clear to the employees what the goals, mission, and vision of the company are in orderto deal with the challenges, propose an action plan to minimize the challenges encountered,and be able to effectively implement the total quality management concepts.
Keywords: Business